About technologies of use of external data on creating and editing of encyclopedic texts - Proskudina, G.Yu.; Kudim, K.A. (PROBLEMS IN PROGRAMMING, 2018)
The paper discusses developing of  Wikidata project, the query web service and the query language. The workflow of the web service, query language and result output forms are demonstrated with plenty of examples. Wikidata usage technology by third-party systems is developed.In this concern ExternalData extension which is part of MediaWiki software is considered. Additionally the instruction for installation and configuration of  the extension is presented. During test period ExternalData extension was improved. procedure for automatic list generation in wiki page is developed.Problems in programming 2017; 1: 67-82